Israel : Staff Report for the 2009 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2010)
This staff report discusses Israel's 2009 Article IV Consultation on economic developments and policies. The economy has been shielded from the global downturn by the absence of prior housing or bank credit booms, high household savings rates, and the fact that investment goods and consumer durables are mostly imported from abroad. Safe-haven factors that have put upward pressure on the currency appear to have eased along with the global financial sector stabilization, and concerns about the excessive strength of the shekel have not entirely been put to rest.